Identification of the Most Cost-effective Position of Vedolizumab Among the Available Biologic Drugs for the Treatment of Ulcerative Colitis. (4th January 2020) - Scott, Frank I; Luo, Michelle; Shah, Yash; Lasch, Karen; Vajravelu, Ravy K; Mamtani, Ronac; Fennimore, Blair; Gerich, Mark E; Lewis, James D
Abstract: Background and Aims: There are limited data on the most cost-effective sequencing of biologics for ulcerative colitis [UC]. Methods: We used Markov modelling to identify the most cost-effective position for vedolizumab among biologics for steroid-dependent UC, with a base-case of a 35-year-old male. We assessed three treatment algorithms, with vedolizumab use: prior to an initial anti-tumour necrosis factor alpha [anti-TNFα] and azathioprine [Algorithm 1]; prior to a second anti-TNF and azathioprine [Algorithm 2]; and prior to colectomy [Algorithm 3]. The initial anti-TNF could be either infliximab or adalimumab. Transition probabilities, costs, and quality-adjusted life-year estimates were derived from published estimates, Medicare, and the Nationwide Inpatient Sample. Primary analyses included 100 trials of 100 000 individuals over 1 year, with a willingness-to-pay threshold of US$100, 000. Multiple sensitivity analyses were conducted to assess our findings. Results: From a population perspective, when both infliximab and adalimumab are available, vedolizumab was preferred as the first biologic if ≥14% of initial anti-TNF use was adalimumab. If infliximab is the primary biologic, vedolizumab use after infliximab [Algorithm 2] and prior to adalimumab was the most cost-effective strategy. All models were sensitive to biologic pricing. Conclusions: This simulation demonstrated that the most cost-effective strategy in UC depends on the proportion of patients using adalimumab as the initial anti-TNF. If adalimumab was ≥14%, vedolizumab was preferred as the first biologic. When only infliximab was available for first-line therapy, the most cost-effective position of vedolizumab was prior to cycling to adalimumab.